Environmental Violence, Displacement, and Postcolonial Trauma in Nigeria's Niger Delta: A Reading of Helon Habila's Oil on Water - Azetu Azashi Agyo (Journal of linguistics, culture and communication, 2026)
The Niger Delta crisis in southern Nigeria has produced profound ecological devastation and entrenched human suffering, yet its literary and psychological dimensions remain insufficiently theorised within African trauma studies and postcolonial literary criticism. This study investigates Helon Habila's Oil on Water (2010), a work of hybrid narrative fiction documenting the environmental violence, political displacement, and communal disintegration wrought by petroleum extraction in Nigeria's oil-producing south, as a site of literary, political, and ethical inquiry. The study aims to analyse how Habila constructs his narrative as an act of literary witness that transforms individual and ecological suffering into collective political testimony, while foregrounding a distinctly petro-spatial configuration of trauma shaped by environmental collapse, institutional abandonment, and necropolitical governance. Employing a qualitative, text-based methodology grounded in close reading, the study draws on trauma theory, frameworks of complex PTSD, necropolitics, and the concept of atmospheric violence. The findings reveal that petro-trauma in the text operates through ecological disintegration, psychic fragmentation, and the structural erasure of communal identity — symptoms of a postcolonial state and multinational extractive order that render oil-producing populations simultaneously indispensable and expendable. The study contributes to African ecocriticism and postcolonial literary scholarship by establishing Oil on Water as a significant text in the genre of literary witness, while proposing extractive capitalism and corporate complicity as productive analytical trajectories in postcolonial African conflict literature. Ultimately, the study affirms that literature remains an indispensable counter-archive of political memory and a vehicle for challenging dominant discourses of petroleum wealth.